Method of making particulate composition
By storing polymer particles in aqueous dispersions at ≤0°C and grinding at low energy at a temperature higher than the glass transition temperature, the problems of high energy and cost-intensive frozen grinding processes in the prior art are solved, and efficient manufacturing is achieved. The polymer composition with particles less than 1.00 mm and improves the roundness of the particle shape.
Patent Information
- Application Number
- CN202380048769.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-03
- Filing Date
- 2023-06-16
- Publication Date
- 2025-02-07
AI Technical Summary
Prior art In the production of polymer compositions with particles less than 1.00 mm, high energy and cost-intensive freezing milling processes are required, and the surface of the grinded particles is rough.
By providing an aqueous dispersion, containing polymer particles having a specific glass transition temperature, and stored at a temperature of ≤0°C until precipitation is formed, then grinding at a low energy level above the polymer glass transition temperature, obtaining a Particle compositions with a high percentage of particles less than 1.00 mm.
A particle composition with a particle size less than 1.00 mm is achieved with very little mechanical energy input, and the particles have a rounder primary particle shape, avoiding the high cost and energy-intensiveness of the frozen grinding process.
Smart Images

Figure CN119403864A_ABST
Abstract
Description
[0001] The present invention relates to a method for producing a particle composition, comprising: I) providing an aqueous dispersion comprising polymer particles, wherein the polymer of the particles has a glass transition temperature determined by differential scanning calorimetry at a heating and cooling rate of 20 K / min according to ISO 11357; and II) storing the dispersion in step I) at a temperature of ≤0° C. until a precipitate comprising the polymer is formed.
[0002] The invention also relates to a particle composition obtainable by the method, and to the use of the particle composition as a building material in an additive manufacturing process, as a coating or an adhesive.
[0003] The processing of polymers with defined particle sizes is a core requirement for many different applications and industries. Fine polymer powders are used for powder scattering applications or in sintering processes. Industries using these materials include the textile and footwear industry, the automotive industry as well as the medical and cosmetics industries. The size requirements for polymer particles used in the above applications are often in the sub-millimeter range.
[0004] The state of the art in the grinding of solid or liquid materials is extensive and includes many different grinding systems using the rotor / stator principle, such as toothed colloid mills. These systems are usually used to process highly viscous materials or emulsions.
[0005] Depending on their properties, materials can be milled / ground in their dry or wet state. The advantages of wet grinding over dry grinding are that material handling and dosing are easier and that no dust is generated when the material is processed. However, these processes use large amounts of solvents / water that can evaporate and require careful monitoring if solvents are used.
[0006] Especially for the milling of thermoplastic polyurethanes (TPU), cryogenic milling / grinding is the method of choice. In this technique, the materials are cooled to below their glass transition temperature to ensure that they are in a glassy state. Since TPUs are usually soft and tough at room temperature and heat up with energy input during milling, they tend to agglomerate or stick to containers and rotors. This is undesirable. Typically, coolants such as liquid CO2 or N2 are used in amounts of up to 10 kg per 1 kg of milled polymer. This makes cryogenic milling / grinding an energy-intensive, costly and complex process.
[0007] In WO 2020 / 085912 A1, a method for preparing thermoplastic polymers is disclosed, wherein the examples disclose polymer particles obtained, for example, by cryogenic milling. Prior to milling, the thermoplastic polymers in WO 2020 / 085912 A1 are dried at elevated temperature and, in most cases, under vacuum.
[0008] In US 2008 / 171208 A1, it is disclosed that dispersion "2" (comparative) and dispersion "4" (according to the invention in US 2008 / 171208 A1) were stored in a freezer at -5°C for 24 hours and the polymer precipitated in the form of coarse solid particles. The formulation was heated to room temperature and the precipitated polymer was separated from the slurry by filtration. The polymer was then dried and ground in a jet mill under cooling.
[0009] It should be noted that in WO 2020 / 085912 A1 and US 2008 / 171208 A, the polymer particles are dried before grinding.
[0010] WO 2021 / 233749 A1 relates to a method for manufacturing a solid-incorporated polymer, comprising the following steps: I) providing an aqueous polymer dispersion, the dispersion comprising crystalline polyurethane particles having an average particle size of ≤500 nm, and further comprising inorganic particles; II) storing the dispersion of step I) at a temperature of ≤0°C until a precipitate is formed; III) separating the precipitate of step II), and IV) removing water from the precipitate separated in step III) to obtain a dehydrated precipitate. The present disclosure also relates to a solid particle composition obtainable by the method, and the use of the composition as a building material in an additive manufacturing process, as a coating, an adhesive, or as a rubber.
[0011] WO 2021 / 233750 A1 discloses a method for manufacturing a solid-incorporated polymer, comprising the following steps: I) providing an aqueous polymer dispersion comprising crystalline polyurethane particles having a particle size of ≤500 nm; and further comprising organic colorant particles; II) storing the dispersion of step I) at a temperature of ≤0°C until a precipitate is formed; III) separating the precipitate of step II), and IV) removing water from the precipitate separated in step III) to obtain a dehydrated precipitate. The present disclosure also relates to a solid particle composition obtainable by the method, and the use of the composition as a building material in an additive manufacturing process, as a coating or an adhesive.
[0012] The object of the present invention is to provide a method for producing a granular composition with increased grinding efficiency by a low-energy milling process. The increased efficiency can be determined in particular by the percentage of particles having a size of less than 1.00 mm, preferably less than 0.50 mm, more preferably less than 0.25 mm. This object has been achieved by a method according to claim 1. The invention also provides a granular composition according to claim 12 and the use of a granular composition according to claim 15. Advantageous embodiments are disclosed in the dependent claims. They can be freely combined unless the context clearly indicates otherwise.
[0013] Thus, a method of making a granular composition comprises:
[0014] I) providing an aqueous dispersion comprising polymer particles, wherein the polymer of the particles has a glass transition temperature determined by differential scanning calorimetry with double heating at a heating and cooling rate of 20 K / min according to ISO 11357, and
[0015] II) The dispersion from step I) is stored at a temperature of ≤0° C. until a precipitate comprising the polymer is formed.
[0016] The method further comprises:
[0017] III) grinding the precipitate of step II) at a temperature above the glass transition temperature of the polymer to obtain a particle composition, wherein the ground precipitate has a water content of at least 5% by weight.
[0018] Surprisingly, the particle composition obtained by the process of the present invention has a high percentage of particles with a size of less than 1.00 mm. An advantage of the process of the present invention is that, even at temperatures above the glass transition temperature of the polymer particles, a particle composition with a particle size of less than 1.00 mm can be achieved with minimal mechanical energy input, which particles can otherwise only be obtained by energy and cost intensive processes such as cryo-grinding. Another advantage of the process of the present invention is that the process provides particles with a more rounded primary particle shape, in contrast to particles from cryo-grinding processes, which provide materials with mostly fractal, rough surfaces.
[0019] The aqueous dispersion containing polymer particles provided in step I) can be based on commercially available polymer dispersions. The polymer particles dispersed in the aqueous phase can have an intensity-based harmonic mean particle size (Z-average) of a hydrodynamic diameter of ≤1000nm or ≤500nm determined by dynamic light scattering. The preferred average particle size is ≥10nm to ≤500nm, ≥10nm to ≤350nm, more preferably ≥20nm to ≤350nm and ≥20nm to ≤250nm. The dispersion may also contain conventional adjuvants such as emulsifiers. In addition, the dispersion may have an acid, base or buffer system to set the pH value to a desired level. A pH value of 4 to 10 is preferred. Finally, a water-soluble electrolyte such as a metal halide, an oxide or a carbonate may be added to affect the electrostatic properties of the polymer particles such as zeta potential.
[0020] The polymer of the particles has a glass transition temperature (hereinafter also referred to as "Tg"), which is determined by differential scanning calorimetry with double heating at a heating and cooling rate of 20 K / min according to ISO 11357. Preferably, the polymer of the particles has a Tg of -70°C to 20°C, more preferably -70°C to 0°C, in particular -70°C to -20°C, and most preferably -70°C to -30°C.
[0021] In step II) of the method, the polymer-containing dispersion is stored at a temperature of 0°C or lower, preferably -5°C or lower, more preferably -10°C or lower, and most preferably above the glass transition temperature of the polymer particles, until a precipitate containing the polymer is formed. The precipitate contains agglomerates of the polymer particles. In a simple but effective manner, step II) can be performed by storing drums or other common commercial transport containers of the polymer dispersion (such as IBC (intermediate bulk containers), big bags, etc.) in a walk-in freezer or commercial refrigeration facility. Preferably, common transport pallets such as Europallets can be used to transport the containers.
[0022] Optionally, water-soluble ions based on alkali or alkaline earth metals or acid or base may be added to the aqueous dispersion to promote the formation of the precipitate.
[0023] The median particle size of the granular composition may be ≤1 mm, more preferably ≤0.8 mm, especially ≤0.5 mm by weight distribution.
[0024] In step III), the precipitate of step II) is ground at a temperature above the glass transition temperature of the polymer to obtain a particle composition. The ground precipitate has a water content of at least 5% by weight, based on the total weight of the precipitate.
[0025] Grinding can be carried out by various suitable machines, such as ball mills, powder mills or hammer mills. Preferably, grinding is carried out by internal grinding of the precipitated polymer particles themselves, wherein the stirring and grinding equipment only promotes this internal grinding of the polymer particles. In this regard, in addition to high-power grinding equipment that is efficient in reducing the particle size to the desired value in <5 minutes, preferably <2 minutes, more preferably <1 minute, it is also feasible to use simple, low-power and slow stirring, with a processing time of up to two days.
[0026] The energy input for grinding the precipitate may be lower than conventional processing, for example at least ≤50%, more preferably ≤40%, especially ≤30% and most preferably ≤20% of the energy input for standard freeze grinding operations of tough polymeric materials.
[0027] Preferably, in the granule composition after step III), the content of particles having a size of less than 1.00 mm determined by graded sieving is between 60% by weight and 100% by weight, based on the total weight of the particles. Preferably, 70% by weight to 100% by weight, particularly 80% by weight to 100% by weight, and most preferably 85% to 100%. Further preferably, in the granule composition after step III), the content of particles having a size of less than 0.50 mm determined by graded sieving is between 20% by weight and 100% by weight, based on the total weight of the particles. Preferably, 40% by weight to 100% by weight, particularly 60% by weight to 100% by weight, and most preferably 85% by weight to 100% by weight.
[0028] The granular composition can be prepared in the presence of a polymer reactive material, such as a blocked or free isocyanate containing compound, a carbodiimide, epoxide, amine, carboxylic acid or aziridine containing compound. Preferably, the reactive compound is introduced in liquid or solid or particulate solid form and stirred with the polymer dispersion in step I) for a period of time to achieve a homogeneous distribution before the polymer dispersion is stored at a temperature of <0°C in step II). In a preferred aspect, the reactive compound contains a free isocyanate with a melting point of >30°C. Preferably, the free isocyanate containing compound comprises an aliphatic isocyanate, preferably PDI, HDI or IPDI. Preferably, the free isocyanate containing compound is a particulate solid before being stirred into the polymer dispersion.
[0029] In one variant, which variant can be freely combined with other embodiments described herein unless the context clearly indicates otherwise, the method for making a granular composition according to the present invention comprises:
[0030] I) providing an aqueous dispersion comprising polymer particles, wherein the polymer of the particles has a glass transition temperature determined by differential scanning calorimetry with double heating at a heating and cooling rate of 20 K / min in accordance with ISO 11357,
[0031] II) storing the dispersion from step I) at a temperature of ≤ 0°C until a precipitate comprising the polymer is formed, and
[0032] III) grinding the precipitate of step II) at a temperature above the glass transition temperature of the polymer to obtain a particle composition, wherein the precipitate of step II) has a water content of at least 5% by weight.
[0033] According to one embodiment, the method further comprises concentrating the polymer particles to 70 to 90% by weight of the precipitate and continuing with step III). Concentration can be achieved by removing most of the aqueous phase by draining to obtain a (wet) precipitate having a residual water content of 10 to 30% by weight and 70 to 90% by weight of polymer particles based on the total weight for further processing. Conventional solid-liquid separation methods can be used. Preferred methods for increasing the concentration of polymer particles in the dispersion are filtration, decantation, dehydration pressing, partial drying or a combination thereof. The residual aqueous phase may have a solid content of ≤5.0% by weight, preferably ≤2.0% by weight, more preferably ≤1.0% by weight, and most preferably ≤0.5% by weight.
[0034] According to another embodiment, the method further comprises: IV) removing water from the granular composition obtained after step III) to obtain a dried granular composition. Step IV) is an optional drying step, wherein the water content of the granular composition can be further reduced. This can produce a free-flowing powder or granules. Drying can be carried out by heating, dry air treatment and / or application of vacuum and by vacuum and / or dry extrusion. The dried granular composition preferably has a water content of less than 5% by weight based on the total weight of the dried granular composition.
[0035] According to another embodiment, the dry granular composition of step IV) has a water content of ≥0.05 wt.% to ≤5 wt.%, based on the total weight of the dry granular composition. Preferably, the water content is >0.05 wt.% to 2.00 wt.%, and more preferably the water content is >0.10 wt.% to <1.00 wt.%.
[0036] According to another embodiment, step III) is carried out at a temperature ≤ 0°C and above the glass transition temperature of the polymer particles. Preferably, this grinding in step III) is carried out at a temperature of -50°C to 0°C, more preferably at -40°C to -8°C.
[0037] According to another embodiment, step III) is carried out at a temperature >0°C and above the glass transition temperature of the polymer particles. Preferably, this grinding in step III) is carried out at a temperature of 2°C to 40°C, more preferably at 5C to 25C.
[0038] According to another embodiment, the precipitate has a water content of not less than 5% by weight before step III). This embodiment shall exclude (partial) drying and re-wetting of the material before being subjected to grinding.
[0039] According to another embodiment, the precipitate in step II) has a water content of ≥10 to ≤70 wt.-%. Preferably, the water content is between 12 wt.-% and 60 wt.-%, in particular between 15 wt.-% and 60 wt.-%, and most preferably between 25 wt.-% and 60 wt.-%.
[0040] According to another embodiment, the polymer particles comprise thermoplastic polymer particles. Preferably, at least 30 wt. %, more preferably at least 50 wt. %, even more preferably at least 95 wt. % of the polymer particles relative to the total amount of polymer particles are thermoplastic polymer particles.
[0041] According to another embodiment, the thermoplastic polymer particles are thermoplastic polyurethane particles. Examples of suitable polymer particles include anionic hydrophilic polyurethanes, cationic hydrophilic polyurethanes and nonionic hydrophilic polyurethanes. Polyurethanes without internal hydrophilic groups can be emulsified by adding external emulsifiers to the dispersion. Preferred emulsifiers are based on nonionic polyethylene glycol.
[0042] Likewise suitable are linear polyester polyurethanes prepared by reacting a) polyester diols having a molecular weight of more than 600 and optionally b) diols having a molecular weight of 62 to 600 g / mol as chain extenders with c) aliphatic diisocyanates, observing an equivalent ratio of hydroxyl groups of components a) and b) to isocyanate groups of component c) of 1:0.9 to 1:0.999, wherein component a) consists of at least 80% by weight of polyester diols having a molecular weight of 1500 to 3000 based on (i) adipic acid and (ii) 1,4-dihydroxybutane and / or neopentyl glycol.
[0043] Further preferably, component c) comprises IPDI and / or HDI and / or H12MDI. Also preferably, alkanediol b) is selected from the group consisting of 1,2-dihydroxyethane, 1,3-dihydroxypropane, 1,4-dihydroxybutane, 1,5-dihydroxypentane, 1,6-dihydroxyhexane or a combination of at least two of these in an amount of up to 200 hydroxyl equivalent percent based on component a).
[0044] Polyurethanes may also contain urea groups and are therefore also regarded as polyurethane / polyurea compounds.
[0045] The polyurethanes are preferably crystalline, i.e. they are at least partially crystallized after the dispersion has been dried. By reheating the melting peak present in a differential scanning calorimetry (DSC) measurement at a heating / cooling rate of 20 K / min, at least partial crystallinity of the material can be established. The melting peak of the polyurethane material is preferably at a temperature of 20° C. to 100° C., more preferably at a temperature of 40° C. to 80° C.
[0046] In another embodiment of the invention, the aqueous dispersion contains a polyurethane having a melting point below 100° C. and a glass transition temperature (Tg) determined by DSC with a heating and cooling rate of 20 K / min and in the range of −70° C. to <0° C.
[0047] According to another embodiment, the polymer of the polymer particles in the aqueous dispersion of step I) has a number average molecular weight Mn of ≥10,000 g / mol, determined by gel permeation chromatography with THF as eluent on polystyrene standards. Preferably Mn ≥20,000 g / mol, and in particular ≥30,000 g / mol. This is particularly preferred in the case of polyurethane polymers. Polymers with such high molecular weights can usually only be processed to stable dispersions at low target solids contents. This has no effect in the process according to the invention, since the material will precipitate anyway.
[0048] According to another embodiment, the aqueous dispersion of step I) has a polymer solids content of ≥10 wt.-% to ≤60 wt.-%, based on the total weight of the aqueous dispersion. According to commercially available polymer dispersions, the polymer particle content is preferably ≥30 wt.-% to ≤55 wt.-%.
[0049] Another aspect of the present invention is a granular composition obtained by the method of the present invention. According to one embodiment, the content of particles with a size less than 0.50 mm determined by graded sieving is between 20% by weight and 100% by weight based on the total weight of the particles. Preferably, the range is between 40% by weight and 100% by weight, particularly preferably between 60% by weight and 100% by weight, and most preferably between 85% by weight and 100% by weight. In another embodiment, the granular composition has an average weight distribution particle size of ≤1 mm and is an aliphatic TPU having a melting point of ≤100° C. determined by DSC at a heating and cooling rate of 20K / min by secondary heating.
[0050] Another aspect of the present invention is the use of the granular composition according to the invention as a coating or adhesive.
[0051] The granular composition may also be combined and used in combination with a powdered crosslinking agent to form a reactive powder, wherein the crosslinking agent is preferably a solid isocyanate, a solid blocked isocyanate, a solid carbodiimide, or a solid aziridine or a solid epoxide. Example
[0052] The present invention will be further described with reference to the following examples and drawings, but is not intended to be limited by these examples and drawings.
[0053] Material
[0054] Deionized water was used in all experiments.
[0055] Polyester Polyurethane Polymers:
[0056] Dispersion A is an aqueous crystalline polyester polyurethane / urea dispersion for adhesive applications having a pH of 6.9, a polymer glass transition temperature of 51° C. (DSC, 20 K / min), a polymer melting temperature of 49° C. (DSC, 20 K / min) and a solids content of about 50% by weight.
[0057] The starting distribution (Example A1) was prepared from Dispersion A as follows: 1 kg of Dispersion A in a 1 liter plastic container was frozen at -18°C for 48 hours and thawed at room temperature for 24 hours. Then, a coarse particle slurry of white polymer crumb in water was wet classified as described below.
[0058] The starting distribution (Example A2) was prepared from dispersion A as follows: 1) 1 kg of dispersion A in a 1 liter plastic container was frozen at -18°C for 48 hours and thawed at room temperature for 24 hours. 2) The resulting coarse particle slurry of white polymer crumb rubber in water was filtered to obtain a solid material with a water content of about 20% by weight. It was then wet classified as described.
[0059] The starting distribution (Example A3) was prepared from dispersion A by the following steps: 1) 1 kg of dispersion A in a 1 liter plastic container was frozen at -18°C for 48 hours and thawed at room temperature for 24 hours. 2) The resulting coarse particle slurry of white polymer crumb rubber in water was filtered to obtain a solid material with a water content of about 20% by weight. 3) The material was vacuum dried in a rotary evaporator to obtain a solid material with a water content of about 13% by weight. Wet classification was then performed as described.
[0060] The starting distribution (Example A4) was prepared from dispersion A as follows: 1) 1 kg of dispersion A in a 1 liter plastic container was frozen at -18°C for 48 hours and thawed at room temperature for 24 hours. 2) The resulting coarse particle slurry of white polymer crumb rubber in water was filtered to obtain a solid material with a water content of about 20% by weight. 3) The material was vacuum dried in a rotary evaporator to obtain a solid material with a water content of about 0.5% by weight. Dry classification was then performed as described.
[0061] Inventive Example B was prepared from Dispersion A in a two-step process: 1) 1 kg of Dispersion A in a 1 liter plastic container was frozen at -18°C for 48 hours and thawed at room temperature for 24 hours. 2) The resulting coarse particle slurry of white polymer crumb rubber in water was ground for 2 minutes at 23°C (room temperature) using a GEFU 89210 Flotte Lotte grinder. Wet classification was then performed as described.
[0062] Inventive Example C was prepared from Dispersion A in a three-step process: 1) 1 kg of Dispersion A in a 1 liter plastic container was frozen at -18°C for 48 hours and thawed at room temperature for 24 hours. 2) The resulting coarse particle slurry of white polymer crumb rubber in water was filtered to obtain a solid material having a water content of about 20% by weight. 3) The wet polymer crumb rubber was ground for 2 minutes at 23°C (room temperature) using a GEFU 89210 Flotte Lotte grinder. Wet classification was then performed as described.
[0063] Inventive Example D was prepared from Dispersion A in a three-step process: 1) 1 kg of Dispersion A in a 1 liter plastic container was frozen at -18°C for 48 hours and thawed at room temperature for 24 hours. 2) The resulting suspension of white polymer crumb rubber in water was filtered to obtain a solid material having a moisture content of about 13%. 3) The wet polymer crumb rubber was ground for 2 minutes at 23°C (room temperature) using a GEFU 89210 Flotte Lotte grinder. Wet classification was then performed as described.
[0064] Example E was prepared from dispersion A as follows: 1) 210 kg of dispersion A in a 220 liter polypropylene drum was frozen at -18°C for 14 days and thawed at 25°C for 14 days. 2) The resulting coarse particle slurry of white polymer crumb rubber in water was filtered and dried in an industrial-scale multi-purpose container with a capacity of about 300 liters. A total of 125 kg of wet material was loaded into the container. After removing free-flowing water by filtration to a residual moisture content of about 30% by weight, a pressure of 20-30 mbar was applied at a mantle temperature of the container at 30°C. After drying to a moisture content of about 0.5%, the polymer material was removed from the container and analyzed by dry sieving.
[0065] Inventive Example F was prepared in a similar manner to Example E. After filtering the resulting coarse particle slurry of 125 kg of white polymer crumb rubber in water to a water content of about 30% by weight, a vacuum of 20-30 mbar was applied at a hood temperature of the container of 30° C., while the material was additionally stirred for 24 hours at an average stirring speed of 7-20 rpm. The geometry of the stirrer was such that it did not primarily shear the polymer, since the stirrer was located 2 cm from the container wall, but moved itself (316L paddle stirrer). After drying to a water content of about 0.5%, the polymer material was removed from the container and subjected to dry sieve analysis.
[0066] Reference Example G was obtained from Reference Sample A4 by sieving for 10 minutes using 4 mm and 1 mm sieves. The weight % of the material fraction between 4 mm and 1 mm was then used as the starting distribution for Comparative Examples H and I.
[0067] Comparative Example H used the material produced in Reference Example G. The dry polymer crumb rubber was ground for 2 minutes using a GEFU 89210 Flotte Lotte grinder. It was then dry classified as described.
[0068] Comparative Example I used the material produced in Reference Example G. In addition, the dried polymer particles were suspended in water (volume ratio 1 / 1) for 5 minutes to rewet them, and then the rewetted polymer crumb rubber was ground for 2 minutes at 23° C. (room temperature) using a GEFU 89210 Flotte Lotte grinder. Wet classification was then carried out as described.
[0069] Inventive Example J used the frozen material produced in Reference Example A1 without thawing. The frozen polymer / water slurry was cut into 3 cm cubes with a saw. About 300 g was ground at Level 10 for 1 minute using a high shear Thermomix Kitchen Machine (TM5). Wet classification was then performed as described.
[0070] Comparative Example K used material produced in Reference Example G. The dry polymer crumbs were ground using a high shear Thermomix KitchenMachine (TM5) at 23°C (room temperature) for 1 minute at Level 10. They were then dry classified as described.
[0071] Material L is a fine powder obtained by fraction sieving for 10 minutes in Example B of the present invention, and sieves are performed to obtain a sieve fraction of 250 μm to 100 μm.
[0072] Comparative Example Example M is a fine powder obtained by the latest freeze grinding technology of A4 (cooling with liquid nitrogen in a pen mill) and subsequent 10 minutes of fraction sieving to obtain a sieve fraction of 250 microns to 100 microns.
[0073] The material fractions L and M were then used for a) microanalysis and b) flow behavior analysis, respectively.
[0074] method
[0075] Room temperature (RT) is 23° C. Unless otherwise stated, all percentages are by weight based on the total weight.
[0076] Using a food grinder "GEFU 89210 Flotte Lotte" with a 1 mm perforated disc, grind / mill about 200 g (calculated as dry weight) of the material. Grind manually at 10-15 rpm for 2 minutes, while returning the material deposited on the edges to the bottom every 30 seconds to ensure homogeneous grinding of the material. After 1 minute and 50 seconds, rinse the remaining material with 500 ml of deionized water and then grind for 10 seconds. The "filtrate" and "residue" are then remixed.
[0077] About 150 g of material (calculated on dry weight) of frozen dispersion A (frozen at -18°C for 48 hours) was subjected to high shear grinding / milling for 1 minute at Level 10 in a Thermomix Kitchen Machine TM5 to obtain broken and still frozen polymer particles. The received particles were thawed with 500 ml of deionized water and then wet classified as described below.
[0078] Sieve analysis was performed on a Haver & Boecker test sieving shaker using stacked analysis sieves with the following mesh sizes: 4 mm, 1 mm, 500 μm, 250 μm and 100 μm. Sieving was performed at an amplitude of 1 for 10 minutes at room temperature.
[0079] Wet fractionation was performed as follows: a water spray nozzle was placed on top of a 4 mm sieve, with 1 mm, 500 mm, 250 μm and 100 μm sieves fitted below. Flushing was performed until the liquid discharged through the receiver was clear (about 7 liters). All wet fractions were dried at 40° C. until their residual moisture content was <1% by weight. The dry fraction was measured gravimetrically (in % by weight) based on the total (dry) mass used.
[0080] The scale-up experiments (Examples E+F) were carried out on a multifunctional vacuum filtration unit model (HV Drucknutsche V260-FA03) comprising a 300 liter container. The container was equipped with a 316 liter paddle stirrer. Thawed material was used throughout the experiments. To filter / drain excess water, the container was loaded and covered with 3 bar nitrogen for 1 hour to remove free-flowing water through a 0.1 mm mesh screen. The solid content after draining was about 70% by weight.
[0081] For Example E, a vacuum of 20-30 mbar was applied at 30°C to dry the material.
[0082] In the case of Example F, the material was stirred at 20 rpm (revolutions per minute) at a temperature not exceeding 35° C. for 24 hours.
[0083] The residual moisture content was measured using the "mass loss" method. The measurements were performed using a HE73 moisture analyzer (Mettler Toledo) at 125°C with a stop criterion of 1 mg / 75 s.
[0084]
[0085]
[0086] As can be seen from reference examples A1, A2, A3 and A4, the freezing and thawing process of each polyurethane dispersion (average particle size of the dispersion <1 μm) can lead to particle agglomeration. For evaluation, the screening results are assigned to the polymer particle fractions greater than and less than 1 mm in size. In the absence of any mechanical stress / grinding, the distribution ratio of polymer crumb rubber in A1 (<1 mm / >1 mm) is about 0.5. As can be seen from the results of reference examples A2, A3 and A4, whether filtering / draining free-flowing water (20% residual water by weight), partially dried samples (about 13% residual water by weight) or dried samples (about 0.5% residual water by weight), the size distribution does not change significantly. Example A4 shows a slight shift to larger agglomerates, which may be related to some melting of particles during vacuum drying, resulting in some agglomeration. Surprisingly, after only 2 minutes of grinding frozen and thawed materials (Example B) and drained and partially dried materials (Examples C, D), the size distribution has changed significantly. The number of particles with a size <1 mm has increased by more than double. The ratio (<1mm / >1mm) increased from <0.6 to >3.5.
[0087] In another setup, the material was processed at an industrial scale to demonstrate the scalability of the process. Again, Reference E shows the size distribution of the material without any grinding step. This size distribution is comparable to the results obtained at laboratory scale. Alternatively, the material in Example F was stirred at 20 rpm for 24 hours, which again resulted in a significant shift in the size distribution towards smaller particles.
[0088] As a comparative example, the following experiment was conducted: First, a 4 mm to 1 mm fraction was produced from Reference Example A4 by sieving for 1 minute. Sample G still contained a small amount (2.9%) of particles smaller than 1 mm by analytical sieving for 10 minutes and evaluation.
[0089] Example H was prepared by grinding sample G in a GEFU 89210 Flotte Lotte for 2 minutes. Surprisingly, the results after sieve analysis did not show a shift to smaller particles. On the contrary, the size distribution remained comparable to Example G.
[0090] This suggests that the dried polymer itself is dimensionally stable and cannot be ground further given the low stress conditions. In Experiment I, sample G was dispersed in the same volume of water for 5 minutes to investigate whether rewetting could reduce the size of the polymer particles to that of the original wet state. However, after grinding this composition, it is clear from the size distribution that again no shift to smaller sizes is obtained, as it is comparable to reference G.
[0091] To demonstrate that reference sample A1 can be ground even in a frozen state (<0°C) (no thawing occurred), the material was exposed to high shear forces using a Thermomix Kitchen Machine. (Example J). The results clearly show that as the ratio (<1 mm / >1 mm) increases from <0.6 to >40, the particle size decreases significantly.
[0092] To further demonstrate that high shear alone is not suitable for grinding dry materials, Example K was performed. Here, G was ground using a Thermomix Kitchen Machine with high shear (2 minutes, level 10), and no increase in ratio was observed.
[0093] To further demonstrate the feasibility of this process for applications that typically require expensive and energy intensive cryo-milling to obtain powders <1 mm required for applications such as powder scattering or laser sintering, fractions of samples Al, B, E, F, J were investigated in depth. For the above applications, particle sizes less than 500 μm are desirable. Sizes less than 150 μm are most desirable.
[0094] Table 2 - Detailed analysis of each sieve fraction
[0095]
[0096] * Reference or comparative example
[0097] Comparing reference A1 with example B, it can be seen that A1 contains no particles <250 μm and only about 12% of the particles are below the given threshold of 500 μm. In contrast, example B contains 22% of the desired particles between 500 μm and 250 μm. In addition, it is possible to produce about 15% of particles with a size <250 μm. A small fraction of particles <100 μm is also obtained.
[0098] The scaled-up examples show similar trends. Also in reference E, about 12% of the particles have a size below 500 μm. The distribution is comparable to A1. In example F, a significant shift towards lower particle sizes is observed. A main fraction of 43% <100 μm can be produced by low-energy stirring, making it a very interesting alternative to cryogenic grinding. Moreover, when high shear grinding is performed in the frozen state (example J), about 75% of the particles have a size of <500 μm as desired, and even 16.7% of the particles have a size below 100 μm.
[0099] The mass average size further shows that the particle size decreases as the average values of A1 and E are reduced by more than half in their respective counterparts B, F and J.
[0100] The mass average size is calculated as
[0101] To further evaluate the shape of the fine powder samples obtained by freeze grinding (M) and wet grinding (L), both samples were sieved analytically using 250 μm and 100 μm sieves, which gave comparable size distributions, and compared by optical microscopy. The microscope was a Keyence VHX, using a top light source. The samples were spread on a clear glass slide. The magnification was 200x. Figure 1 Microscope images of cryo-milled particles according to sample M are shown. Figure 2 A microscope image of particles of sample L prepared according to the method of the present invention is shown. Figure 1 and Figure 2 The images shown in clearly depict the difference in particle shape, with the freeze-ground particles showing distinct edges that are less prone to breakage compared to the more rounded and less distinct shapes produced according to the method of the present invention.
[0102] In order to further evaluate the properties of the illustrated examples of the invention, the flow behavior of samples L and M was compared. The analysis was performed on a powder analyzer (Revolution Powder Analyzer, PS Prozesstechnik GmbH) with the settings shown in Table 3.
[0103] Table 3: Powder analyzer settings
[0104]
[0105] The samples were characterized based on the following properties obtained from the powder analyzer:
[0106] Rotational Speed (RPM): The rotational speed is the number of revolutions per minute of the barrel during the analysis. The user sets this rate when creating a mobility method.
[0107] Avalanche Angle (degrees): The software collects the angle of the powder at maximum power before the power avalanche occurs. This measurement is the average of all avalanche angles.
[0108] Avalanche energy (cch, mj or pascal): Avalanche energy refers to the energy released by avalanche in sample powder.
[0109] Fracture energy (mJ): Fracture energy is the maximum energy level of the sample powder before avalanche starts.
[0110] Surface fractal: Surface fractal is the fractal dimension of the powder surface, which reflects the roughness of the powder surface.
[0111] Density (g / cm 3 ): For each digital image taken, the software measures the density of the sample.
[0112] Table 4: Comparison of samples L and M obtained from the powder analyzer
[0113]
[0114]
[0115] Table 4 (continued): Comparison of samples L and M obtained from the powder analyzer
[0116]
[0117]
[0118] The results in Table 4 show that the powder quality produced by Example L of the present invention has good flowability and is very similar to state-of-the-art freeze-milled powders.
[0119] Surprisingly, wet-milled Sample L exhibited lower fracture energy (preferred) and lower surface fractal (preferred) compared to Sample M at all rotation speeds.
Claims
1. A method for producing a granular composition, comprising: 1) providing an aqueous dispersion comprising polymer particles, wherein the polymer of the particles has a glass transition temperature determined by differential scanning calorimetry with double heating at a heating and cooling rate of 20 K / min according to ISO 11357; II) storing the dispersion in step I) at a temperature of ≤0° C. until a precipitate comprising a polymer is formed; Features The method further comprises: III) grinding said precipitate of step II) at a temperature above the glass transition temperature of the polymer to obtain a particle composition, wherein said ground precipitate has a water content of at least 5% by weight.
2. The method according to claim 1, characterized in that The method further comprises concentrating the polymer particles to 70 to 90 wt % of the precipitate and continuing with step III).
3. The method according to claim 1 or 2, characterized in that: The method further comprises: IV) removing water from the granular composition obtained after step III) to obtain a dry granular composition.
4. The method according to claim 3, wherein the dry granular composition of step IV) has a moisture content of ≥ 0.05 wt. % to ≤ 5 wt. %, based on the total weight of the dry granular composition.
5. The method according to any one of claims 1 to 4, characterized in that Step III) is carried out at a temperature of ≤ 0°C and above the glass transition temperature of the polymer particles.
6. The method according to any one of claims 1 to 4, characterized in that Step III) is carried out at a temperature >0°C and above the glass transition temperature of the polymer particles.
7. The method according to any one of claims 1 to 6, characterized in that Prior to step III), the precipitate has a water content of not less than 5% by weight.
8. The method according to any one of claims 1 to 7, characterized in that The precipitate in step II) has a water content of ≥10 to ≤70% by weight.
9. The method according to any one of claims 1 to 8, characterized in that The polymer particles include thermoplastic polymer particles.
10. The method according to claim 9, characterized in that The thermoplastic polymer particles are thermoplastic polyurethane particles.
11. The method according to any one of claims 1 to 10, characterized in that The polymer of the polymer particles in the aqueous dispersion of step I) has a number average molecular weight Mn of ≥ 10000 g / mol as determined by gel permeation chromatography with THF as eluent against polystyrene standards.
12. The process according to any one of claims 1 to 11, wherein the aqueous dispersion of step I) has a polymer solids content of ≥10 wt.-% to ≤60 wt.-%, based on the total weight of the aqueous dispersion.
13. A granular composition obtainable by the process according to any one of claims 1 to 12.
14. The granular composition according to claim 13, wherein the content of particles having a size of less than 0.50 mm as determined by fractional sieving is from 20% by weight to 100% by weight based on the total weight of the particles.
15. Use of the granular composition according to claim 13 or 14 as a coating or adhesive.
Citation Information
Patent Citations
Adhesives
US20080171208A1
Polyester powders and the use thereof in three-dimensional printing processes
WO2020085912A1
Method of manufacturing filled polyurethane particles
WO2021233749A1
Method of manufacturing colorant-filled polyurethane particles
WO2021233750A1